2019
DOI: 10.1101/791368
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ATP-driven separation of liquid phase condensates in bacteria

Abstract: Liquid-liquid phase separated (LLPS) states are key to compartmentalise components in the absence of membranes, however it is unclear whether LLPS condensates are actively and specifically organized in the sub-cellular space and by which mechanisms. Here, we address this question by focusing on the ParAB S DNA segregation system, composed of a centromeric-like sequence ( parS ), a DNA-binding protein (ParB) and a motor (ParA). We show that parS -ParB associate to form nanometer-sized, spherical droplets. ParB … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…Instead it may be advantageous to form a more compact partition complex to better facilitate the partitioning function of ParABS. Indeed, while F plasmid ParB spreads over a four times larger region than ParB of C. crescentus (11), the resultant partition complex is significantly smaller (a radius (2σ) of 35 nm) (49). Thus, we speculate that plasmid-based ParABS systems may operate in the more compact globular region.…”
Section: Discussionmentioning
confidence: 92%
“…Instead it may be advantageous to form a more compact partition complex to better facilitate the partitioning function of ParABS. Indeed, while F plasmid ParB spreads over a four times larger region than ParB of C. crescentus (11), the resultant partition complex is significantly smaller (a radius (2σ) of 35 nm) (49). Thus, we speculate that plasmid-based ParABS systems may operate in the more compact globular region.…”
Section: Discussionmentioning
confidence: 92%
“…It was suggested that ATP supply is necessary for maintaining liquid‐like behavior in nucleoli and SGs. [ 25,29,128,173 ] Dramatically decreased ATP levels can induce a liquid‐to‐solid transition and change the overall cytoplasmic state in bacteria and yeast. [ 174,175 ] ATP‐related proteins such as helicases and chaperone proteins are commonly implicated in controlling the material properties of RNP granules.…”
Section: Regulation Of Phase Separationmentioning
confidence: 99%
“…studied ParABS, a system responsible for chromosome and plasmid segregation in bacteria. [ 128 ] While the ParB protein drove phase separation, they found that ParA, specifically ParA's ATPase activity, was necessary to control the size and location of ParABS condensates. Similar mechanisms may also play a role in other condensates, including P granules [ 129 ] and stress granules, [ 130,131 ] where the enzymatic activity has been shown to dissolve condensates.…”
Section: Limitations On Condensate Coarseningmentioning
confidence: 99%